2016
DOI: 10.5539/jms.v6n4p35
|View full text |Cite
|
Sign up to set email alerts
|

Solid Waste Management Trends in Nigeria

Abstract: The purpose of this paper is to investigate the current trend of solid waste management in Nigeria and to identify the major challenges inhibiting the attainment of sustainable solid waste management in the country. The study relied on a desktop study approach; hence, data were obtained from previous publications relevant to the current study, particularly from peer reviewed publications. Sources such as waste management agencies websites, reports and documents, journal articles, environmental organizations re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 27 publications
(93 reference statements)
0
11
0
Order By: Relevance
“…To this effect, Longe et al (2009) advise the adoption of waste reduction, recycling and reuse as an alternative. 2.1.4 Constraints and Remedies of the traditional solid waste management The overall management of solid waste in Nigeria is poor (Amasuomo & Baird, 2016). Various studies (Oyeniyi, 2011;Oguntoyinbo, 2012;Amuda et al, 2014;Olukanni et al, 2016) have highlighted various challenges facing SWM in Nigeria across various states.…”
Section: Solid Waste Disposal/treatmentmentioning
confidence: 99%
“…To this effect, Longe et al (2009) advise the adoption of waste reduction, recycling and reuse as an alternative. 2.1.4 Constraints and Remedies of the traditional solid waste management The overall management of solid waste in Nigeria is poor (Amasuomo & Baird, 2016). Various studies (Oyeniyi, 2011;Oguntoyinbo, 2012;Amuda et al, 2014;Olukanni et al, 2016) have highlighted various challenges facing SWM in Nigeria across various states.…”
Section: Solid Waste Disposal/treatmentmentioning
confidence: 99%
“…The site selection for the landfill will involve geologic formation of the site which will be determined during the environmental impact assessment process. Amasuomo and Baird (2017) noted that studies conducted on some landfills in Nigeria showed that the…”
Section: Final Disposalmentioning
confidence: 99%
“…The consistently low quantities spread across African communities suggests that more awareness and education is required to enlighten the public on waste management responsibility. The literature associates the consistent low quantities of waste disposed of to landfill sites as a function of policy, collaborative government services and public sensitisation on waste management hierarchy (Amasuomo, 2016). Dladla et al (2016) examined the factors that are associated with the prevalence of indiscriminate dumping of waste in communities and elucidated cause-effects between these factors.…”
Section: Introductionmentioning
confidence: 99%